Predicting the global economic costs of biological invasions by tetrapods - Thomas W. Bodey; Ross N. Cuthbert; Christophe Diagne; Clara Marino; Anna Turbelin; Elena Angulo; Jean Fantle-Lepczyk; Daniel Pincheira-Donoso; Franck Courchamp; Emma J. Hudgins (Science of The Total Environment, 2025)

Economic costs of non-native species in Türkiye: A first national synthesis - Ali Serhan Tarkan; Esra Bayçelebi; Daniela Giannetto; Emine Demir Özden; Ayşe Yazlık; Özgür Emiroğlu; Sadi Aksu; Ahmet Uludağ; Necmi Aksoy; Hazel Baytaşoğlu; Cüneyt Kaya; Tanju Mutlu; et al. (Journal of Environmental Management, 2024)

The economic costs of invasive aquatic plants: A global perspective on ecology and management gaps - Rafael L. Macêdo; Phillip J. Haubrock; Gabriel Klippel; Romina D. Fernandez; Boris Leroy; Elena Angulo; Laís Carneiro; Camille L. Musseau; Odete Rocha; Ross N. Cuthbert (Science of The Total Environment, 2024)

Linear and Non-linear Analyses of EEG in a Group of ASD Children During Resting State Condition - Brenda Y. Angulo-Ruiz; Francisco J. Ruiz-Martínez; Elena I. Rodríguez-Martínez; Anca Ionescu; David Saldaña; Carlos M. Gómez (Brain Topography, 2023)
This study analyses the spontaneous electroencephalogram (EEG) brain activity of 14 children diagnosed with Autism Spectrum Disorder (ASD) compared to 18 children with normal development, aged 5–11 years. (i) Power Spectral Density (PSD), (ii) variability across trials (coefficient of variation: CV), and (iii) complexity (multiscale entropy: MSE) of the brain signal analysis were computed on the resting state EEG. PSD (0.5–45 Hz) and CV were averaged over different frequency bands (low-delta, delta, theta, alpha, low-beta, high-beta and gamma). MSE were calculated with a coarse-grained procedure on 67 time scales and divided into fine, medium and coarse scales. In addition, significant neurophysiological variables were correlated with behavioral performance data ( Kaufman Brief Intelligence Test (KBIT) and Autism Spectrum Quotient (AQ)). Results show increased PSD fast frequency bands (high-beta and gamma), higher variability (CV) and lower complexity (MSE) in children with ASD when compared to typically developed children. These results suggest a more variable, less complex and, probably, less adaptive neural networks with less capacity to generate optimal responses in ASD children.

Long-term recovery of Mediterranean ant and bee communities after fire in southern Spain - J. Manuel Vidal-Cordero; Elena Angulo; Francisco P. Molina; Raphaël Boulay; Xim Cerdá (Science of The Total Environment, 2023)

Multiscale entropy of ADHD children during resting state condition - Brenda Y. Angulo-Ruiz; Vanesa Muñoz; Elena I. Rodríguez-Martínez; Celia Cabello-Navarro; Carlos M. Gómez (Cognitive Neurodynamics, 2023)
This present study aims to investigate neural mechanisms underlying ADHD compared to healthy children through the analysis of the complexity and the variability of the EEG brain signal using multiscale entropy (MSE), EEG signal standard deviation (SDs), as well as the mean, standard deviation (SDp) and coefficient of variation (CV) of absolute spectral power (PSD). For this purpose, a sample of children diagnosed with attention-deficit/hyperactivity disorder (ADHD) between 6 and 17 years old were selected based on the number of trials and diagnostic agreement, 32 for the open-eyes (OE) experimental condition and 25 children for the close-eyes (CE) experimental condition. Healthy control subjects were age- and gender-matched with the ADHD group. The MSE and SDs of resting-state EEG activity were calculated on 34 time scales using a coarse-grained procedure. In addition, the PSD was averaged in delta, theta, alpha, and beta frequency bands, and its mean, SDp, and CV were calculated. The results show that the MSE changes with age during development, increases as the number of scales increases and has a higher amplitude in controls than in ADHD. The absolute PSD results show CV differences between subjects in low and beta frequency bands, with higher variability values in the ADHD group. All these results suggest an increased EEG variability and reduced complexity in ADHD compared to controls.

Habitats diversity and MPA regulations are insufficient in promoting healthy coral reef fish assemblages in Punta Francés National Park (Cuba) - Zenaida M. Navarro-Martínez; Elena de la Guardia; William A. Szelistowski; Jorge A. Angulo-Valdés (Regional Studies in Marine Science, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Economic costs of protecting islands from invasive alien species - Thomas W. Bodey; Elena Angulo; Alok Bang; Céline Bellard; Jean Fantle‐Lepczyk; Bernd Lenzner; Anna Turbelin; Yuya Watari; Franck Courchamp (Conservation Biology, 2023)
Biological invasions represent a key threat to insular systems and have pronounced impacts across environments and economies. The ecological impacts have received substantial focus, but the socioeconomic impacts are poorly synthesized across spatial and temporal scales. We used the InvaCost database, the most comprehensive assessment of published economic costs of invasive species, to assess economic impacts on islands worldwide. We analyzed socioeconomic costs across differing expenditure types and examined temporal trends across islands that differ in their political geography—island nation states, overseas territories, and islands of continental countries. Over US$36 billion in total costs (including damages and management) has occurred on islands from 1965 to 2020 due to invasive species’ impacts. Nation states incurred the greatest total and management costs, and islands of continental countries incurred costs of similar magnitude, both far higher than those in overseas territories. Damage‐loss costs were significantly lower, but with qualitatively similar patterns across differing political geographies. The predominance of management spending differs from the pattern found for most countries examined and suggests important knowledge gaps in the extent of many damage‐related socioeconomic impacts. Nation states spent the greatest proportion of their gross domestic products countering these costs, at least 1 order of magnitude higher than other locations. Most costs were borne by authorities and stakeholders, demonstrating the key role of governmental and nongovernmental bodies in addressing island invasions. Temporal trends revealed cost increases across all island types, potentially reflecting efforts to tackle invasive species at larger, more socially complex scales. Nevertheless, the already high total economic costs of island invasions substantiate the role of biosecurity in reducing and preventing invasive species arrivals to reduce strains on limited financial resources and avoid threats to sustainable development goals.

Habitat-dependent variation in consistent behavioural traits does not affect the efficiency of resource acquisition in a thermophilic ant - Swetashree Kolay; Raphaël Boulay; Elena Angulo; Patrizia d’Ettorre; Xim Cerdá (Behavioral Ecology and Sociobiology, 2023)

Economic costs of invasive alien ants worldwide - Elena Angulo; Benjamin D. Hoffmann; Liliana Ballesteros-Mejia; Ahmed Taheri; Paride Balzani; Alok Bang; David Renault; Marion Cordonnier; Céline Bellard; Christophe Diagne; Danish A. Ahmed; Yuya Watari; et al. (Biological Invasions, 2022)
Invasive ants are amongst the most destructive and widespread invaders across the globe; they can strongly alter invaded ecosystems and are responsible for the loss of native ant species. Several studies have reported that invasive ants can also lead to substantial economic costs. In this study, we search, describe and analyse 1342 reported costs of invasive ants compiled in the InvaCost database. Economic costs, reported since 1930 for 12 ant species in 27 countries, totalled US$ 51.93 billion, from which US$ 10.95 billion were incurred, and US$ 40.98 billion were potential costs (i.e., expected or predicted costs). More than 80% of total costs were associated with only two species, Solenopsis invicta and Wasmannia auropunctata ; and two countries, the USA and Australia. Overall, damage costs amounted to 92% of the total cost, mainly impacting the agriculture, public and social welfare sectors. Management costs were primarily post-invasion management (US$ 1.79 billion), with much lower amounts dedicated to prevention (US$ 235.63 million). Besides the taxonomic bias, cost information was lacking for an average of 78% of the invaded countries. Moreover, even in countries where costs were reported, such information was available for only 56% of the invaded locations. Our synthesis suggests that the global costs of invasive ants are massive but largely biased towards developed economies, with a huge proportion of underreported costs, and thus most likely grossly underestimated. We advocate for more and improved cost reporting of invasive ants through better collaborations between managers, practitioners and researchers, a crucial basis for adequately informing future budgets and improving proactive management actions of invasive ants.

Surprisingly high economic costs of biological invasions in protected areas - Desika Moodley; Elena Angulo; Ross N. Cuthbert; Brian Leung; Anna Turbelin; Ana Novoa; Melina Kourantidou; Gustavo Heringer; Phillip J. Haubrock; David Renault; Marine Robuchon; Jean Fantle-Lepczyk; et al. (Biological Invasions, 2022)
Biological invasions are one of the main threats to biodiversity within protected areas (PAs) worldwide. Meanwhile, the resilience of PAs to invasions remains largely unknown. Consequently, providing a better understanding of how they are impacted by invasions is critical for informing policy responses and optimally allocating resources to prevention and control strategies. Here we use the InvaCost database to address this gap from three perspectives: (i) characterizing the total reported costs of invasive alien species (IAS) in PAs; (ii) comparing mean observed costs of IAS in PAs and non-PAs; and (iii) evaluating factors affecting mean observed costs of IAS in PAs. Our results first show that, overall, the reported economic costs of IAS in PAs amounted to US$ 22.24 billion between 1975 and 2020, of which US$ 930.61 million were observed costs (already incurred) and US$ 21.31 billion were potential costs (extrapolated or predicted). Expectedly, most of the observed costs were reported for management (73%) but damages were still much higher than expected for PAs (24%); in addition, the vast majority of management costs were reported for reactive, post-invasion actions (84% of management costs, focused on eradication and control). Second, differences between costs in PAs and non-PAs varied among continents and environments. We found significantly higher IAS costs in terrestrial PA environments compared to non-PAs, while regionally, Europe incurred higher costs in PAs and Africa and Temperate Asia incurred higher costs in non-PAs. Third, characterization of drivers of IAS costs within PAs showed an effect of environments (higher costs in terrestrial environments), continents (higher in Africa and South America), taxa (higher in invertebrates and vertebrates than plants) and Human Development Index (higher in more developed countries). Globally, our findings indicate that, counterintuitively, PAs are subject to very high costs from biological invasions. This highlights the need for more resources to be invested in the management of IAS to achieve the role of PAs in ensuring the long term conservation of nature. Accordingly, more spatially-balanced and integrative studies involving both scientists and stakeholders are required.

Activation-Inhibition dynamics of the oscillatory bursts of the human EEG during resting state. The macroscopic temporal range of few seconds - Carlos M. Gómez; Brenda Y. Angulo-Ruíz; Vanesa Muñoz; Elena I. Rodriguez-Martínez (Cognitive Neurodynamics, 2022)
The ubiquitous brain oscillations occur in bursts of oscillatory activity. The present report tries to define the statistical characteristics of electroencephalographical (EEG) bursts of oscillatory activity during resting state in humans to define (i) the statistical properties of amplitude and duration of oscillatory bursts, (ii) its possible correlation, (iii) its frequency content, and (iv) the presence or not of a fixed threshold to trigger an oscillatory burst. The open eyes EEG recordings of five subjects with no artifacts were selected from a sample of 40 subjects. The recordings were filtered in frequency ranges of 2 Hz wide from 1 to 99 Hz. The analytic Hilbert transform was computed to obtain the amplitude envelopes of oscillatory bursts. The criteria of thresholding and a minimum of three cycles to define an oscillatory burst were imposed. Amplitude and duration parameters were extracted and they showed durations between hundreds of milliseconds and a few seconds, and peak amplitudes showed a unimodal distribution. Both parameters were positively correlated and the oscillatory burst durations were explained by a linear model with the terms peak amplitude and peak amplitude of amplitude envelope time derivative. The frequency content of the amplitude envelope was contained in the 0–2 Hz range. The results suggest the presence of amplitude modulated continuous oscillations in the human EEG during the resting conditions in a broad frequency range, with durations in the range of few seconds and modulated positively by amplitude and negatively by the time derivative of the amplitude envelope suggesting activation-inhibition dynamics. This macroscopic oscillatory network behavior is less pronounced in the low-frequency range (1–3 Hz).

Correction to: Behavioral responses to numerical differences when two invasive ants meet: the case of Lasius neglectus and Linepithema humile - Gema Trigos-Peral; Sílvia Abril; Elena Angulo (Biological Invasions, 2021)

Behavioral responses to numerical differences when two invasive ants meet: the case of Lasius neglectus and Linepithema humile - Gema Trigos-Peral; Sílvia Abril; Elena Angulo (Biological Invasions, 2021)
Two of the world’s most invasive ants, Linepithema humile and Lasius neglectus, are destined to overlap in range as they continue to spread throughout Europe. Although L. humile arrived first, and is therefore more numerically abundant, L. neglectus is the more behaviorally dominant of the two. We performed lab trials to determine whether L. humile could use numerical abundance to overcome the behavioral dominance of L. neglectus and whether the ants’ behavioral patterns shifted when the species co-occurred. We found that L. neglectus was more aggressive when less abundant, whereas the opposite was true of L. humile . When L. neglectus was outnumbered, it employed aggressive behaviors, such as biting or chemical attacks, more frequently than L. humile ; it also utilized a behavioral sequence that included mandible opening and biting. Our results for these species support the hypothesis that species modulate their behavior towards competitors, which facilitates the understanding of how multiple invasive ant species can co-occur in a given area. Moreover, our study shows that the co-occurrence of invasive species could result from the use of two strategies: (1) the Bourgeois strategy, in which aggressiveness changes based on numerical dominance and (2) the dear-enemy strategy, in which aggressiveness is reduced when competitors co-occur. Since these strategies may lead to territory partitioning, we suggest that the behavioral flexibility displayed by both species when they overlap may allow local co-occurrence and increase their likelihood of co-occurrence during their range expansion in Europe, which could have a negative cumulative impact on invaded areas.

Effects of the Argentine ant venom on terrestrial amphibians - Paloma Alvarez‐Blanco; Xim Cerdá; Abraham Hefetz; Raphaël Boulay; Alejandro Bertó‐Moran; Carmen Díaz‐Paniagua; Alain Lenoir; Johan Billen; H. Christoph Liedtke; Kamlesh R. Chauhan; Ganga Bhagavathy; Elena Angulo (Conservation Biology, 2021)
Invasive species have major impacts on biodiversity and are one of the primary causes of amphibian decline and extinction. Unlike other top ant invaders that negatively affect larger fauna via chemical defensive compounds, the Argentine ant ( Linepithema humile ) does not have a functional sting. Nonetheless, it deploys defensive compounds against competitors and adversaries. We estimated levels of ant aggression toward 3 native terrestrial amphibians by challenging juveniles in field ant trails and in lab ant foraging arenas. We measured the composition and quantities of toxin in L. humile by analyzing pygidial glands and whole‐body contents. We examined the mechanisms of toxicity in juvenile amphibians by quantifying the toxin in amphibian tissues, searching for histological damages, and calculating toxic doses for each amphibian species. To determine the potential scope of the threat to amphibians, we used global databases to estimate the number, ranges, and conservation status of terrestrial amphibian species with ranges that overlap those of L. humile . Juvenile amphibians co‐occurring spatially and temporally with L. humile die when they encounter L. humile on an ant trail. In the lab, when a juvenile amphibian came in contact with L. humile the ants reacted quickly to spray pygidial‐gland venom onto the juveniles. Iridomyrmecin was the toxic compound in the spray. Following absorption, it accumulated in brain, kidney, and liver tissue. Toxic dose for amphibian was species dependent. Worldwide, an estimated 817 terrestrial amphibian species overlap in range with L. humile , and 6.2% of them are classified as threatened. Our findings highlight the high potential of L. humile venom to negatively affect amphibian juveniles and provide a basis for exploring the largely overlooked impacts this ant has in its wide invasive range.

Breeding consequences for a songbird nesting in Argentine ant’ invaded land - Paloma Alvarez-Blanco; Juli Broggi; Xim Cerdá; Oscar González-Jarri; Elena Angulo (Biological Invasions, 2020)

Humans and scavenging raptors facilitate Argentine ant invasion in Doñana National Park: no counter-effect of biotic resistance - Sara Castro-Cobo; Soledad Carpintero; Joaquín L. Reyes-López; Fabrizio Sergio; Elena Angulo (Biological Invasions, 2019)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Native predators living in invaded areas: responses of terrestrial amphibian species to an Argentine ant invasion - Paloma Alvarez-Blanco; Stephane Caut; Xim Cerdá; Elena Angulo (Oecologia, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Early developmental processes limit socially mediated phenotypic plasticity in an ant - Irene Villalta; Olivier Blight; Elena Angulo; Xim Cerdá; Raphaël Boulay (Behavioral Ecology and Sociobiology, 2016)

Plastic changes in tadpole trophic ecology revealed by stable isotope analysis - Stéphane Caut; Elena Angulo; Carmen Díaz-Paniagua; Ivan Gomez-Mestre (Oecologia, 2013)

Ant community structure on a small Pacific island: only one native species living with the invaders - Xim Cerdá; Elena Angulo; Stéphane Caut; Franck Courchamp (Biological Invasions, 2012)

Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Elena Angulo; Stéphane Caut; Xim Cerdá (Biological Invasions, 2011)

Avoiding surprise effects on Surprise Island: alien species control in a multitrophic level perspective - Stéphane Caut; Elena Angulo; Franck Courchamp (Biological Invasions, 2009)

Individual and collective foraging decisions: a field study of worker recruitment in the gypsy ant Aphaenogaster senilis - Xim Cerdá; Elena Angulo; Raphaël Boulay; Alain Lenoir (Behavioral Ecology and Sociobiology, 2009)

Double Allee Effects and Extinction in the Island Fox - ELENA ANGULO; GARY W. ROEMER; LUDĚK BEREC; JOANNA GASCOIGNE; FRANCK COURCHAMP (Conservation Biology, 2007)
An Allee effect (AE) occurs in populations when individuals suffer a decrease in fitness at low densities. If a fitness component is reduced (component AE), per capita population growth rates may decline as a consequence (demographic AE) and extinction risk is increased. The island fox (Urocyon littoralis) is endemic to six of the eight California Channel Islands. Population crashes have coincided with an increase in predation by Golden Eagles (Aquila chrysaetos). We propose that AEs could render fox populations more sensitive and may be a likely explanation for their sharp decline. We analyzed demographic data collected between 1988 and 2000 to test whether fox density (1) influences survival and reproductive rates; (2) interacts with eagle presence and affects fox fitness parameters; and (3) influences per capita fox population trends. A double component AE simultaneously influenced survival (of adults and pups) and proportion of breeding adult females. The adult survival AE was driven by predation by eagles. These component AEs led to a demographic AE. Multiple‐component AEs, a predation‐driven AE, and the simultaneous occurrence of both component and demographic AEs in a mammal are all previously unreported processes. Populations below 7 foxes/km 2 could have suboptimal population growth rates due to the demographic AE, and AEs may have contributed to the dramatic declines in three fox populations. Because fox densities in critically endangered populations are well below this level, removing Golden Eagles appears necessary to prevent a predation‐driven AE. Conservationists should also be aware of AEs when planning the release of captive foxes. More generally, our findings highlight the danger of overlooking AEs in the conservation of populations of rare or threatened species.